The Influence of Principal Leadership and School Culture on the Quality of Educational in Tenggarong Senior High Schools - Nuryasmi, Nuryasmi; Komariyah, Laili; Masruhim, Amir; Gede Mulawarman, Widyatmike; Haeruddin, Haeruddin; Bahzar, Moh (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Principal leadership and school culture are important aspects that can affect the quality of services in various educational institutions. these two aspects support in improving the quality of education which can be seen from the quality of educational services in a school. This study aims to determine the effect of principal leadership and school culture on the quality of educational services at State Senior High Schools in Tenggarong. Multiple linear regression is an approach to modeling the relationship between a dependent variable and one or more independent variables. This study uses multiple linear regression methods with sampling techniques using simple random sampling. The research site of 3 senior high schools in Tenggarong with a total population of 287 students, while the sample taken was 167 students. Data is collected through a questionnaire, which has been conduct for the validity and reliability test. The results showed that overall, these two factors contributed simultaneously to the quality of education services with a coefficient of determination of 76%, while the remaining 24% was influenced by other factors not identified in the model in this study. Data were collected through questionnaires that have been tested for validity and reliability. The results showed that overall, these two factors contributed simultaneously to the quality of education services with a coefficient of determination of 76%, while the remaining 24% was influenced by other factors not identified in the model in this study. The results show that principal leadership has a significant effect of 0.742 on the quality of education services, while school culture has a significant effect of 0.661 on the quality of education services in 3 Tenggarong high schools. The importance of synergy between principal leadership and school culture has a positive impact on the ability of human resources in the school, so that the quality of service and quality of education can be improved.